PEMBUATAN POLIGLISIDIL NITRAT DARI GLISEROL HASIL SAMPING INDUSTRI BIODIESEL: STUDI TERMODINAMIKA DAN KINETIKA REAKSI - , ERNA ASTUTI, S.T., M.T., Ir. Supranto, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Development of national defense industry is a must in an effort to supply the needs of the means of defense. The existence of national defense industry support the independence of Indonesia in the field of defense. One indicator of self-reliance in defense technology is the procurement of propellant as rocket fuel. The constraint of rocket development is the availability of propellant. Propellant Industry is underdeveloped in Indonesia so that the propellant must be imported. Polyglicidyl nitrate (PGN) which can be used as a propellant binder can be made from glycerol obtained as a byproduct of the biodiesel industry. The glycerol that was produced needed alternative way to handling immediately so as to not become the waste that polluted the environment. The general aim of this study is to obtain design data and optimum conditions for plant design of PGN. The focus of this research are study each steps (nitration,ciclyzation and polymerization), develop kinetics model and get thermodynamics and kinetics data. Experiments were done for all steps of the reaction, was begun from nitration and was finished by polymerization. Before all experiments were done, the research about method of analysis was done. This experiments have to do to prove that qualitative analysis with gas chromatography can be used to quantitave analysis of all products of nitration. All experiments were run in reactor which has volume 5 mL and equipped with Hickman distillation head and nitrogen purge. Reactor was immersed in the cooling bath with cooling water temperature was set at the desired temperature of the nitration. Each sample was analyzed by gas chromatography to determine the composition of products. The research of nitration was carried out with variations mole ratio of nitric acid / glycerol 1/1 to 7/1, reaction temperature of 10 to 30°C and nitric acid concentration of 69%. Experimental data were used in simulations to get kinetics parameter. The variables of the cyclization are mole ratio of sodium hydroxide/glycerol of 1/1 to 1.5/1, reaction temperature of 10 to 20°C and sodium hydroxide concentration of 15 to 20%. The stirring time was also calculated for the cyclization. Polymerization was conducted using 1,4-butanediol as initiator and boron trifluoride tetrahidrafuran (BF3.THF) as catalyst, the mole ratio of initiator and catalyst is 1/1, reaction temperature of 15 °C and reaction time is 2 hours. The recommended operating conditions for the production of PGN are: the nitration: the reaction temperature of 20°C, mole ratio of nitric acid/glycerol of 5/1 and the concentration of nitric acid of 69%. Cyclization: reaction temperature of 15°C, mole ratio of sodium hydroxide/glycerol of 1.5 /1 and the concentration of sodium hydroxide of 15%. Polymerization: use BF3.THF as catalyst, the reaction temperature of 13 to 15°C and the mole ratio of catalyst / initiator of 1/1. Glycidyl nitrate conversion by 96.04% and the yield of glycerol at 27.20 PGN% obtained for the reaction time of 2 hours. Nitration reaction consists of several series-parallel reactions. The conversion of 1,3-DNG from 1-MNG is the highest conversion compared to conversion of the other products. Kinetics modeling that was done adequately describe the kinetics of the nitration process. The seven controlling reactions model shows the reactivity difference between primary groups and secondary groups. The primary group is more reactive than the secondary group, seen from the rate constants of reactions involving primary group are larger than rate constants of reactions involving the secondary group. Among all the reactions involving the primary group, the formation of 1,2-DNG reaction from 2-MNG has the largest reaction rate constants. Formation of 1,3-DNG and 1,2-DNG takes place spontaneously, while the reaction of formation of 1-MNG, 2-MNG and TNG does not take place spontaneously. In the nitration products, the 1-MNG and 2-MNG are the most stable while the TNG is most easily decomposed. The three controlling reactions model is more accurate in estimating the nitration experimental results than the seven controlling reactions model nitration reaction and easier to use for design the nitration reactors, but this model cannot predict all of the nitration products. Cyclization consists of nine parallel reactions, where the main reaction is the formation of glycidyl nitrate from 1,3-DNG. The reactions that occur in the cyclization of 1,3-DNG are in accordance with that predicted. Plant design of PGN from glycerol can be done using the three controlling reactions model for the nitration with thermodynamics data: first nitration reaction equilibrium constant (K1) of 0.2559, K2 of 9.0775, K3 of 0.0805 at 20oC temperature and mole ratio of nitric acid/glycerol 5